Effect of glucose on growth and fatty acid composition of an euryhaline eustigmatophyte Nannochloropsis oceanica under mixotrophic culture condition. (September 2018) - Mitra, Madhusree; Mishra, Sandhya
Abstract: We aspire to evaluate the effect of glucose as a carbon source on growth, total lipid yield, polyunsaturated fatty acid and (mainly eicosapentaenoic acid) accumulation of N. oceanica . Microalgal cells were cultured in medium supplemented with different concentrations of glucose (0–40 g L −1 ), and its effect on growth, cellular components including fatty acid compositions was analyzed. We found that even though, N. oceanica displayed a lower growth trend under stress conditions than that of control howbeit showed a marked increase in the cellular lipid contents. The protein and carbohydrate content also get influenced by the glucose stress and because of carbon partitioning. These results could be used to tailor the culture conditions to ameliorate the content of the product of interest. Maximum lipid and eicosapentaenoic acid content were observed at 25 g L −1, while 30 and 40 g L −1 seems to be ideal for attaining higher carbohydrate and protein. Highlights: Glucose stress enhances cellular lipid content. Higher lipid and EPA content were observed at 25 g L −1 . Carbohydrate and protein content increased at 30 g L −1 and 40 g L −1 . Pigment content slightly decreased in the stress condition.